1948
DOI: 10.1017/s0022029900005173
|View full text |Cite
|
Sign up to set email alerts
|

371. The properties of New Zealand butters and butterfats I. Iodine, reichert and saponification values and softening points of monthly samples of butterfats from nine commercial factories over four years

Abstract: With 6 Figures)The variations in the chemical and physical properties of butterfat have already been extensively studied. In many European countries, e.g. Holland, Denmark, Ireland, where examination is made of random samples of butterfats from butters from every factory at intervals throughout the year as part of the regular ' Butter Control Service' to ensure the absence of adulteration with other fats, the information available on the variations in the properties is very complete. Detailed studies of the bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
8
0

Year Published

1949
1949
1992
1992

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 3 publications
5
8
0
Order By: Relevance
“…The C18 unsaturated acids (the major constituents of butterfat) are at a minimum in November (23.4 moles %) and rise to a maximum in May (29.6 moles %), a seasonal variation of 6*2 moles %. The accentuated difference between these two samples does, however, conform to the findings of Cox & McDowall (1948), who observed that seasonal changes in New Zealand butterfats were characterized by low average iodine values in November-December (about 34.0) which rose to relatively high values in May-June (about 40 0).…”
Section: Seasonal Variations In the Proportions Of The Fatty Acid Consupporting
confidence: 87%
See 3 more Smart Citations
“…The C18 unsaturated acids (the major constituents of butterfat) are at a minimum in November (23.4 moles %) and rise to a maximum in May (29.6 moles %), a seasonal variation of 6*2 moles %. The accentuated difference between these two samples does, however, conform to the findings of Cox & McDowall (1948), who observed that seasonal changes in New Zealand butterfats were characterized by low average iodine values in November-December (about 34.0) which rose to relatively high values in May-June (about 40 0).…”
Section: Seasonal Variations In the Proportions Of The Fatty Acid Consupporting
confidence: 87%
“…The saponification equivalents and iodine values, without bearing any direct mathematical relationship with each other, follow the same trends. In conformity with the graphs of Cox & McDowall (1948) saponification equivalents when converted to saponification values exhibit an interrelationship with the Reichert values, an increase in one corresponding with an increase in the other. As might be anticipated, the Reichert values are closely correlated with the proportions of C4-C12 saturated acids found to be present in the samples analysed, and are at a maximum of 32-0 in November and a minimum of 25-5 in May.…”
Section: Relation8hip Between Chemical and Phy8ical Constant8supporting
confidence: 82%
See 2 more Smart Citations
“…3,5). For twin pairs T49, 50 and T71, 72 there was a close within-twin-set relationship for both the fat content of the milk and the yield of fat.…”
Section: Resultsmentioning
confidence: 85%